Творчість Лесі Українки в англомовному світі - Зорівчак, Р. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2008)
Силою і красою лірики, психологічною глибиною і тематичним розмаїттям драматичних творів, тверезістю своїх критичних праць і особистою мужністю Леся Українка зайняла вагоме місце у світовому красному письменстві. Охарактеризовано головних англомовних перекладачів української письменниці та їхній творчий доробок. Зосереджено увагу на тому, що перекладачі намагалися відтворити для читачів не лише зміст творів Лесі Українки, а й їхню форму в усіх видозміннах ритму, рими та віршового розміру. The paper traces the history of the reception of the writings by Lesya Ukrayinka in the English-speaking societies. Through the strength and the beauty of her verse, the psychological depth and thematic range of her dramatic works, the soundness of her critical writings and her personal courage, Lessia Ukrayinka established herself as an artist for all times. The main translators of her writings have been characterized and their contributions highlighted. All the translators were trying to convey to their readers not only the message of Lesya Ukrayinka’s writings but also their form in all its ramifications of rhythm, rhyme and verse structures.